Cemented versus Cementless Stems in Revision Total Knee Arthroplasty - Driesman, Adam S.; Macaulay, William; Schwarzkopf, Ran (The Journal of Knee Surgery, 2019)
Successful arthroplasty of the knee requires a stable foundation for implant placement, adequate mechanical alignment, and durable fixation. In the revision setting, the later may be difficult to obtain, especially in the setting of significant bone loss. While augments, cones, and sleeves have greatly enhanced the modern knee surgeon's ability to gain fixation in metaphyseal bone, stems continue to be a cornerstone tool in revision arthroplasty to bypass deficient or damaged bone surfaces to enhance structural stability of a revision construct. When placing a revision construct, there remains two options to assist with fixation, either fully cementing the entire implant or using a “hybrid” system, which combines an uncemented press-fit diaphyseal stem with cement in both the metaphysis and metaphysis–diaphysis junction of the keel. In this review, we discuss the history of these two techniques, evaluate the theoretical benefits and pitfalls, and assess the best evidence supporting each in the literature. To conclude, we will examine future directions and questions needed to better elucidate the best treatment options in a variety of revision scenarios.
Keywords: adult reconstruction; knee; arthroplasty